2016
DOI: 10.1021/acs.langmuir.6b02291
|View full text |Cite
|
Sign up to set email alerts
|

Pore Size Effect on Methane Adsorption in Mesoporous Silica Materials Studied by Small-Angle Neutron Scattering

Abstract: Methane adsorption in model mesoporous silica materials with the size range characteristic of shale is studied by small-angle neutron scattering (SANS). Size effect on the temperature-dependent gas adsorption at methane pressure about 100 kPa is investigated by SANS using MCM-41 and SBA-15 as adsorbents. Above the gas-liquid condensation temperature, the thickness of the adsorption layer is found to be roughly constant as a function of the temperature. Moreover, the gas adsorption properties, such as the adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…Thus the GPSLM can be applied. The density of methane inside kerogen pores at room temperature can be assumed to be bulk methane density in our cases 32 34 , i.e. (details are given in Supplementary Note 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus the GPSLM can be applied. The density of methane inside kerogen pores at room temperature can be assumed to be bulk methane density in our cases 32 34 , i.e. (details are given in Supplementary Note 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The highly regular pore structure and internal surface area of ordered MS make these particles attractive substrates that can be tailored for NH 3 adsorption [8]. For example, MS particles showed very high uptake capacities and selectivities for CH 4 [9], CO 2 [10], H 2 S [11], NH 3 [12], and volatile organic vapors [13]. Few studies on the removal of hazardous gases by adsorption using MA are reported, even though MA and MS share similar pore properties and high thermal stabilities, as seen in comparison to reports about MS in the literature [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…GPSLM requires the use of contrast variation. To do contrast variation, SLD of the guest fluid, = , in accessible pores can be changed by mixing hydrogenated and deuterated solvents, such as H2O and D2O, with different ratios [28] for neutron scattering or loading gas with different pressures for both X-ray and neutron scattering [33][34][35]. Thus, the GPSLM can be used for both SAXS and SANS even though we use SANS as the example to demonstrate this method.…”
Section: Generalized Porod's Scattering Law Methods (Gpslm)mentioning
confidence: 99%
“…In some works,[39] the surface of large domains is called "envelope" surface. As a simple example, the Porod's scattering from the grain boundaries of mesoporous materials shown at low Q region cannot pick up the mesopore structure because the size of mesopores is too small compared with the Porod's scattering length scale L[33,34,40]. Case 3 can be applied to analyze the Porod's scattering region at low Q for a mixture of mesoporous materials composed of different chemical components.…”
mentioning
confidence: 99%